Study of wake characteristics of a vertical axis wind turbine by two- and three-dimensional computational fluid dynamics simulations. (May 2016) - Lam, H.F.; Peng, H.Y.
Abstract: In this work, the near and far wakes of a low-solidity two-straight-bladed vertical axis wind turbine (VAWT) were, for the first time, investigated with two- and three-dimensional computational fluid dynamics (CFD) simulations. The wake velocity field and turbulence field from 1 to 10 turbine diameters (1D to 10D) downstream were examined. Structured meshes were generated throughout the computational domain for calculation accuracy and efficiency. Both the transition shear stress transport (SST) and the detached eddy simulation (DES) models were used to close the unsteady Reynolds-averaged Navier–Stokes (URANS) equations. The CFD models were validated by particle image velocimetry (PIV) test results from the literature. The regions of the near and far wakes were defined based on the occurrence of the maximum velocity deficit. In the near wake (within 3D), the velocity suffered a drastic deficit of about 85%. In the far wake (beyond 3D), major velocity recovery occurred with the average stream-wise velocity reaching approximately 75% at 10D. The wake asymmetry grew as the downstream distance increased, and the causes behind it were examined. Further, investigation into the dimensional effects of the CFD models, and the blade tip and span vortices was conducted. Highlights: CFD modeling and study of the near and far wakes of a VAWT for the first time. Investigation of the dimensional effects of CFD models on the wake and the loading. Examination of three-component wake motions contributing to the wake evolution. Identification of the evolving wake asymmetry and analysis of the causes. Analysis of the blade tip and blade span vortices and their impacts on the wake.